Uso da toxina botulínica no tratamento de desordens temporomandibulares - Bueno, Guilherme Henrique [UNESP] (2014)
Also called the poison that heals, botulinum neurotoxin extracted from the bacterium Clostridium botulinum, has been causing some controversy and contradiction with respect to its range of non-cosmetic action. Offers to this, the most varied purposes, taking in most of these treatments involving hyperactivity and muscle spasm. It acts by inhibiting the release of acetylcholine from motor nerve endings at the neuromuscular junction, but also has an independent analgesic effect by blocking the action of neurotransmitters such as substance P, glutamate, and calcitonin in peripheral nociceptors. What in practice decreases muscle contraction and eases the pain sensation. It is used to treat various medical conditions, including: strabismus, cervical dystonia, and to urinary incontinence. For the area of operation of the dentist, we have the use of TB in temporomandibular disorders and orofacial pain. It is in literature that using this in combination with other less invasive therapies such as physiotherapy, acupuncture, installation of occlusal splints, among others, represents benefit to the patient in view of its results. There are articles that maintain that the use of TB does not differ from the use of puncture needles on the trigger point or origin of myofascial pain, known as dry needling technique, or the use of simple anesthetic. In which case the use of drugs would be unnecessary. Despite the almost routine use in the treatment of myofascial pain, fewer complications like any other intramuscular injection, to severe complications can occur. We can thus conclude that the use of botulinum toxin may be useful when a proper diagnosis and indication, trying to always opt for the most conservative treatment possible